Improving Law Student Ability on Legal Writing through Critical and Logical Thinking by IRAC Method - Arifin, Ridwan; Alkadri, Riska; Sari, Dewi Puspa; Resthiningsih, Lilies; Holish, Amarru Muftie (Indonesian Journal of Advocacy and Legal Services, 2019)
The lack of good stigma is attached to student activists, ranging from the unsatisfactory level of academic quality, graduating on time, not responsive and very reactive, hard and opposing views, to demonstrations that are colored by violence. The stigma is only in a few cases, not all activists face such conditions, but this stigma seems to have been far attached. The development of student activists today demands that activists must also have three literacy abilities: data literacy, humanitarian literacy, and technological literacy. However, based on the preliminary results of this activity, 90 percent of UNNES Law School student activists agreed that activists must have a critical attitude and critical writing skills, but only about 10 percent of activists who had taken it seriously (thought publications in various forms). This activity is aimed at developing the critical abilities of student activists through increased publications in various media. This activity also aims to establish a critical writing community for student activists and present a concrete forum for channeling ideas and solutions for student activists in writing that can be read by many people. This activity is carried out through a critical thinking approach in legal studies using the IRAC (Issue, Rule, Application, Conclusion) method which is commonly used in analyzing various cases in legal study thinking.